2005
DOI: 10.1007/bf03219020
|View full text |Cite
|
Sign up to set email alerts
|

Transesterification and compatibilization in the blends of bisphenol-A polycarbonate and poly(trimethylene terephthalate)

Abstract: Melt blending of Bisphenol A polycarbonate (PC) and poly(trimethylene terephthalate) (PTT) was carried out over the entire composition range. The mixing time was varied up to 90 min. The resulting samples were analyzed by FT-IR, DSC, XRD, DMTA, 1 H NMR, and SEM. The process of transesterification between the two polymers and their resulting compatibilization were observed. The behaviors of the PTT-rich and PC-rich blends were different and an equilibrium was found to exist. Peculiar behavior, which was differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…It can be ester‐exchanged easily between these two polymers because of the same TT units linked by ester bonds in both TLCP and PTT. This is comparable to our earlier observation that the blend of TLCP (TR4) and poly(butylene terephthalate) revealed transesterification reaction between the polymers blended, and the monomer sequence distribution of the blend tended to close that of a statistical copolymer composed of each repeating units of component polymers . The transesterification can also occur between PTT and polycarbonate at the temperature range often used for melt blending or processing .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…It can be ester‐exchanged easily between these two polymers because of the same TT units linked by ester bonds in both TLCP and PTT. This is comparable to our earlier observation that the blend of TLCP (TR4) and poly(butylene terephthalate) revealed transesterification reaction between the polymers blended, and the monomer sequence distribution of the blend tended to close that of a statistical copolymer composed of each repeating units of component polymers . The transesterification can also occur between PTT and polycarbonate at the temperature range often used for melt blending or processing .…”
Section: Resultssupporting
confidence: 89%
“…In our previous reports, various structure–property relationships of liquid crystalline polyesters were identified for improving compatibility and mechanical properties when blended with engineering plastics . The TLCP blends with engineering plastics such as PET, PTT, and PBT showed improved compatibility and reinforced mechanical properties through a simple chemical interaction such as transesterification .…”
Section: Introductionmentioning
confidence: 99%
“…Various biodiesel blends have existed in the literature, that has some pros and cons. Some of the conventional biodiesel blends and their merits and demerits are explained as follows: hydrogen and algal biodiesel are the blend used in [26], which has increased engine performance and efficiency and further the emission of CO, NO x , CO 2 , HC, and smoke emission is largely reduced. However, it lacks due to the high cost and time consumption and poses a possibility to be unsuccessful.…”
Section: Literature Surveymentioning
confidence: 99%
“…and scenedesmus sp. [25, 26] and converted to bio‐diesel using a two‐step transesterification method and obtain apparently 90% results. However, the oil extraction process is tedious and hence other blends may change extraction steps.…”
Section: Introductionmentioning
confidence: 99%
“…As a reactive compatibilization method, ester–ester and ester–amide exchange reactions have been studied for many years. The reactions for various polymer blends, such as PBS/Polyamide, EVA/PLA, PET/PC, PC/PMMA, etc., were studied, and it was found that some random or graft copolymers were generated by the exchange reactions. The reaction products, which acted as compatibilizer, could effectively improve the compatibility of the blends.…”
Section: Introductionmentioning
confidence: 99%